The Balance of TNF Mediated Pathways Regulates Inflammatory Cell Death Signaling in Healthy and Diseased Tissues - Webster, Joshua D.; Vucic, Domagoj (Frontiers in Cell and Developmental Biology, 2020)
Tumor necrosis factor alpha (TNF; TNF) is a critical regulator of immune responses in healthy organisms and in disease. TNF is involved in the development and proper functioning of the immune system by mediating cell survival and cell death inducing signaling. TNF stimulated signaling pathways are tightly regulated by a series of phosphorylation and ubiquitination events, which enable timely association of TNF receptors-associated intracellular signaling complexes. Disruption of these signaling events can disturb the balance and the composition of signaling complexes, potentially resulting in severe inflammatory diseases.